Risk Assessment of Time and Cost Overrun Factors throughout Construction Project Lifecycle: Pilot Study - Abdul Rahman, Ismail; Binti Ismail, Ismaaini; Musa Jaber, Mustafa (International Journal of Engineering and Technology, 2018)
Construction industry is one of the important contributors to economic development of a country. However, this industry has being facing serious problems such as failure to complete projects within stipulated time and cost. Hence, this paper presents a study on assessing the risk of various factors in causing time and cost overruns throughout the construction life cycle. A pilot study which involved 5 construction experts was conducted to validate the factors and its location in the life cycle. Data collection was carried out using two round Delphi technique with 15 selected respondents.Â  The study found that construction phase is having highest numbers of high risk factors of time and cost overruns.